Influence of sponsor's management style in project prioritization - Luciana Magalh\~aes Girardin Pimentel-Rodrigues; Luciano Ferreira da Silva (Journal of Industrial Engineering and Management (JIEM), 2020)
Purpose: The purpose of this paper is understand how the different styles of sponsor management influence the prioritization of projects. Design/methodology/approach: The empiric analysis used in-depth interviews with 11 executives as method for data collection and qualitative content analysis using theory and data driven categories for analysis is performed. Findings: This research points to the emergence of opportunistic management style, and to evidences of lack of strategic alignment in the project prioritization process. Research limitations/implications: The lack of prioritization methods evidences to compare with project management style. Also, the number of project managers to interview as experts. Practical implications: The analysis shows that committees and post-project evaluation be established to mitigate failures in the prioritization process impacted from sponsor's management styles influence. Originality/value: The paper provides a critical perspective about sponsor's management styles and project prioritization context; it is important to highlight how different management styles of the sponsor result in different behaviors in the companies.
Keywords: 650; management style; sponsor; project prioritization; project management; opportunistic behavior